(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Spent bleaching earth (SBE) was treated with sodium hydroxide (NaOH) and used for the removal of methylene blue (MB). Adsorption test of treated SBE was carried out to evaluate the removal efficiency of MB. It showed that the maximum uptake of MB was at 76.9 mg/g using SBE treated with 3.0 M NaOH which is equivalent to 76% removal of MB. The effect of increasing initial concentration on the removal of MB showed that higher initial concentration leads to higher surface loading which reduces its removal potential. The effect of SBE dosage on the removal of MB pointed to the maximum removal percentage of 95% at 100 mg SBE dosage